Synthesis and Optical Characterization of Silicon Nanowires via Metal-Simulated Chemical Etching - M. W. Alhamd; ‎Hassan Ismail Dambos‎; Mazen Katea Al-Gharrawy (Iraqi Journal of Industrial Research)
This paper presents the findings of a comprehensive study on the characteristics, creation, and optical properties of silicon nanowires (SN) formed through metal-stimulated chemical etching (MSCE) of single-crystal silicon, considering both hole and electronic types of conductivity. Our investigation aims to deepen the understanding of key factors contributing to SN genesis. Notably, a direct correlation has been established between the duration of chemical etching and the resultant silicon nanowire's (SN) length, irrespective of the total etching time. The research encompasses an exploration of various spectral phenomena, including total and specular infrared (IR) reflection, Raman scattering (RS) of light generated by WHs, photoluminescence (PL) spectra, and more. Remarkably, the study reveals a noteworthy linear relationship between the duration of chemical etching and the length of the silicon nanowires. Furthermore, our investigation into diverse spectral phenomena, such as total and specular infrared (IR) reflection, Raman scattering (RS) from light generated by WHs, and photoluminescence (PL) spectra, elucidates intriguing patterns. Specifically, the silicon band in the Raman spectrum demonstrates an increase in size and a migration towards shorter wavelengths with prolonged chemical etching time.